Synthesis of indolo[1,2-c]quinazolines from 2-alkynylaniline derivatives through Pd-catalyzed indole formation/cyclization with N,N-dimethylformamide dimethyl acetal - Arcadi, Antonio; Cacchi, Sandro; Fabrizi, Giancarlo; Ghirga, Francesca; Goggiamani, Antonella; Iazzetti, Antonia; Marinelli, Fabio (Beilstein Journal of Organic Chemistry, 2018)
An efficient strategy for the synthesis of 6-unsubstituted indolo[1,2-c]quinazolines is described. The Pd-catalyzed reaction of o-(o-aminophenylethynyl) trifluoroacetanilides with Ar–B(OH)2 afforded 2-(o-aminophenyl)-3-arylindoles, that were converted to 12-arylindolo[1,2-c]quinazolines by adding dimethylformamide dimethyl acetal (DMFDMA) to the reaction mixture after extractive work-up. This reaction outcome is different from the previously reported Pd-catalyzed sequential reaction of the same substrates with Ar–I, Ar–Br and ArN2+BF4−, that afforded 12-arylindolo[1,2-c]quinazolin-6(5H)-ones. Moreover, 12-unsubstituted indolo[1,2-c]quinazolines can be obtained both by reacting 2-(o-aminophenyl)indoles with DMFDMA or by sequential Pd-catalyzed reaction of o-(o-aminophenylethynyl)aniline with DMFDMA.
Keywords: arylboronic acids; DMFDMA; indoles; indoloquinazolines; quinazolines

(untitled) - Demeunynck, M.; Baussanne, I. (Curr. Med. Chem., 2013)

(untitled) - Tucker, A. M.; Grundt, P. (ARKIVOC, 2012)

(untitled) - Adams, M.; Mahringer, A.; Kunert, O.; Fricker, G.; Efferth, T.; Bauer, R. (Planta Med., 2007)

(untitled) - Hochfellner, C.; Evangelopoulos, D.; Zloh, M.; Wube, A.; Guzman, J. D.; McHugh, T. D.; Kunert, O.; Bhakta, S.; Bucar, F. (J. Appl. Microbiol., 2015)

(untitled) - Vaidya, S. D.; Argade, N. P. (Org. Lett., 2013)

(untitled) - Wang, C.; Zhang, L.; Ren, A.; Lu, P.; Wang, Y. (Org. Lett., 2013)

(untitled) - Nelson, A. C.; Kalinowski, E. S.; Jacobson, T. L.; Grundt, P. (Tetrahedron Lett., 2013)

(untitled) - Sharma, V. M.; Prasanna, P.; Seshu, K. V. A.; Renuka, B.; Rao, C. V. L.; Kumar, G. S.; Narasimhulu, C. P.; Babu, P. A.; Puranik, R. C.; Subramanyam, D.; Venkateswarlu, A.; Rajagopal, S.; et al. (Bioorg. Med. Chem. Lett., 2002)

(untitled) - Rohini, R.; Reddy, P. M.; Shanker, K.; Hu, A.; Ravinder, V. (Eur. J. Med. Chem., 2010)

(untitled) - Rohini, R.; Reddy, P. M.; Shanker, K.; Hu, A.; Ravinder, V. (J. Braz. Chem. Soc., 2010)

(untitled) - Rohini, R.; Shanker, K.; Reddy, P. M.; Sekhar, V. C.; Ravinder, V. (Arch. Pharm., 2009)

(untitled) - Blackman, A. J.; Hambley, T. W.; Picker, K.; Taylor, W. C.; Thirasasana, N. (Tetrahedron Lett., 1987)

(untitled) - Douki, K.; Ono, H.; Taniguchi, T.; Shimokawa, J.; Kitamura, M.; Fukuyama, T. (J. Am. Chem. Soc., 2016)

(untitled) - Frère, S.; Thiéry, V.; Bailly, C.; Besson, T. (Tetrahedron, 2003)

(untitled) - Billimoria, A. D.; Cava, M. P. (J. Org. Chem., 1994)

WO Patent - Dai, X.; Liu, H.; Palani, A.; He, S.; Lai, Z.; Nargund, R.; Marcantonio, K.; Xiao, D.; Brockunier, L. L.; Zorn, N.; Dang, Q.; Peng, X.; et al. (Tetracyclic heterocycle compounds and methods of use thereof for the treatment of hepatitis c, 2014)

(untitled) - Guo, S.; Tao, L.; Zhang, W.; Zhang, X.; Fan, X. (J. Org. Chem., 2015)

(untitled) - Liu, Q.; Yang, H.; Jiang, Y.; Zhao, Y.; Fu, H. (RSC Adv., 2013)

(untitled) - Arcadi, A.; Cacchi, S.; Cassetta, A.; Fabrizi, G.; Parisi, L. M. (Synlett, 2001)

Organopalladium chemistry for Organic Synthesis - Cacchi, S.; Marinelli, F. (John Wiley & Sons, 2002)

(untitled) - Battistuzzi, G.; Cacchi, S.; Fabrizi, G. (Eur. J. Org. Chem., 2002)
See for a review.

(untitled) - Xu, M.; Xu, K.; Wang, S.; Yao, Z.-J. (Tetrahedron Lett., 2013)

(untitled) - Arcadi, A.; Cacchi, S.; Fabrizi, G.; Ghirga, F.; Goggiamani, A.; Iazzetti, A.; Marinelli, F. (Synthesis, 2018)

(untitled) - Arcadi, A.; Cacchi, S.; Fabrizi, G.; Goggiamani, A.; Iazzetti, A.; Marinelli, F. (Org. Biomol. Chem., 2013)

(untitled) - Cacchi, S.; Fabrizi, G.; Pace, P.; Marinelli, F. (Synlett, 1999)

(untitled) - Kidjemet, D. (Synlett, 2002)

(untitled) - Nathubhai, A.; Patterson, R.; Woodman, T. J.; Sharp, H. E. C.; Chui, M. T. Y.; Chung, H. H. K.; Lau, S. W. S.; Zheng, J.; Lloyd, M. D.; Thompson, A. S.; Threadgill, M. D. (Org. Biomol. Chem., 2011)

(untitled) - Utimoto, K.; Miwa, H.; Nozaki, H. (Tetrahedron Lett., 1981)

(untitled) - Iritani, K.; Matsubara, S.; Utimoto, K. (Tetrahedron Lett., 1988)

(untitled) - Arcadi, A.; Cacchi, S.; Fabrizi, G.; Marinelli, F.; Parisi, L. M. (Heterocycles, 2004)

(untitled) - Abbiati, G.; Arcadi, A.; Chiarini, M.; Marinelli, F.; Pietropaolo, E.; Rossi, E. (Org. Biomol. Chem., 2012)